The Role of Urban/Rural Environments on Mexican Children’s Connection to Nature and Pro-environmental Behavior - Duron-Ramos, Maria Fernanda; Collado, Silvia; García-Vázquez, Fernanda Inéz; Bello-Echeverria, Maria (Frontiers in Psychology, 2020)
Living in rural areas has been described as a driver for behaving in a pro-environmental way, mainly due to the more frequent contact with nature that people from rural areas have. However, the processes that link living in a rural area and behaving in a more ecological manner have not been systematically studied. Moreover, most studies have focused on adults living in developed countries. Given the importance that the actions conducted by people in developing countries have for the future of the environment, as well as the relevance of children’s pro-environmentalism for nature conservation, we present a brief research report examining the relationship between Mexican children’s place of residence and self-reported pro-environmental behavior. Participants were 200 children from Mexican rural areas (less than 1.000 inhabitants) and 200 from a Mexican urban city (more than 150.000 inhabitants). Children were between 9 and 12 years old. Children’s connection to nature was considered as a mediator in the relationship between children’s place of residence and pro-environmental behavior. Our findings revealed that rural children hold a stronger sense of connection to nature and behave in a more pro-environmental way than urban children. In addition, the place of residence was directly and positively linked to their pro-environmental behaviors, and this relationship was mediated by children’s connection to nature. The relationship between connection to nature and pro-environmental behavior was stronger for girls than for boys. The model explained 45% of the variance of children’s self-reported pro-environmental behaviors.